KOMPOSISI KOMUNITAS TUMBUHAN BAWAH DI DALAM PLOT PERMANEN 1 HA GUNUNG POHEN CAGAR ALAM BATUKAHU BALI - Sutomo, Sutomo (Metamorfosa: Journal of Biological Sciences, 2015)
A one Ha (100 x 100 m) of Permanent Sampling Plot with 25 subplots (20 x 20 m with 2 x 2 m nested plot) and 5 level rows of altitudinal difference has been established to determine groundcover species stucture and composition in Pohen Mountain, Batukahu Nature Reserve, Bali. Enumeration of all groundcover species revealed that there were 69 species and 47 families with selaginaceae was the most abundant family in the 1 Ha Permanent Sampling Plot. Shannon Index revealed that groundcover species composition in the first, second and third rows were similar, but different with groundcover species composition in the fourth and fifth rows. Cluster Analysis concluded that groundcover species composition were varied. Generally, most of the groundcover species revealed clumped distribution and only a few species were solitaire.
Keywords: permanent sampling plot, groundcover species, stucture and composition, Pohen Mountain, Batukahu Nature Reserve